KONSEP MODEL INTEGRATED WATER RESOURCE MANAGEMENT DALAM PENGELOLAAN SUMBER DAYA AIR BERBASIS KOMUNITAS - Taqwa, Fadhila Muhammad Libasut (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2018)
Indonesian government is obliged to provide continous supply of drinking water. Under the framework of local autonomy regime, water resource management,, including water supply infrastructure, must be done at local authorities responsibility, together with civil society. Therefore, local community is expected to actively involved in the formulation of drinking water development programs. This study compared the water supply management provided by Regional Water Company (PDAM), and the Community based water supply management program which based on Presidential Instruction (IDT) in Tlogo village, Central Java; West Java Provincial government funding model in Buniwangi village, Sukabumi, and Kertamaya, Bogor and CSR/Corporate Social Responsibility models in Cigombong village, Bogor. SWOT methode used to determine the effectiveness of programs implementation and programs sustainability, reviewed by roles of stakeholder, funding, designing, contruction process, operational and maintenance. The result of this study shows that community based programs not yet fulfill the demand and future threaths, and need attentions and cooperation from every stakeholders to be developed. The recommendation for sustainability of water supply management and risk management are shown.